Effect of Conflict Management Styles on Organizational Commitment of University Teachers - Kashif, Mahvish Fatima; Zabrin, Taaba; Tabassum, Rabia (Annals of Human and Social Sciences, 2024)
The major objective of the study was to explore the effect of conflict management styles on organizational commitment of university teachers. Casual comparative research design was used. The population of the study was the teachers of public and private universities of Lahore and the sample for current study was 910 university teachers taken by using stratified random sampling. Strata were made on the basis of institution. Conflict management style scale developed by (Adkins, 2011) was used. The organizational commitment scale was developed by Allen and Meyer (1990). Results of this study showed that the factors of conflict management styles (Collaborating, Competing, Avoiding, and Accommodating) are significantly and positively effecting organizational commitment except compromising. It was recommended that workshops and seminar can be organized for the awareness about conflict management styles for universities teachers.